The Concept of a Transdiscipline: And of Evaluation as a Transdiscipline - Michael Scriven (The Evaluation Center at Western Michigan University, 2008)
There are two main meanings of this term that can be disinterred from the 8,000+ references to their definition in Google (at December 12, 2007), both of them sharing the idea of a discipline that crosses over the boundaries between many other disciplines: we can distinguish them as the 'point of view' sense of the term and the 'method' sense of the term. These senses are not sharply distinct from each other, but are distinct from 'interdiscipline' meaning a compound approach drawing from or working in the boundary area between two or sometimes more other disciplines; and from 'multidiscipline' meaning a compound approach involving more than two other disciplines.